Adapting an attention‐deficit hyperactivity disorder parent training intervention to different cultural contexts: The experience of implementing the New Forest Parenting Programme in China, Denmark, Hong Kong, Japan, and the United Kingdom. Issue 1 (March 2017) - Thompson, Margaret J. J.; Au, Alma; Laver‐Bradbury, Cathy; Lange, Anne‐Mette; Tripp, Gail; Shimabukuro, Shizuka; Zhang, Jin S.; Shuai, Lan; Thompson, Catherine E.; Daley, David; Sonuga‐Barke, Edmund J.
Abstract: The New Forest Parenting Programme (NFPP) is a parenting program developed for parents who have a child with attention‐deficit hyperactivity disorder (ADHD). It is a manualized program that is delivered in a parent's home over 8 weeks, or in a group format, or through a self‐help manual. Three randomized controlled trials have been carried out in the United Kingdom. The NFPP group has adapted the program according to feedback from parents and therapists, and for use with different populations, both within the United Kingdom and internationally. The first international trial took place in New York, United States. Trials in Denmark, Hong Kong, and Japan followed. More recently, a trial of the self‐help manual has been carried out in mainland China. This paper will outline the adaptions that were needed in order to be able to deliver the program in different countries with their own expectations of parenting, culture, and language. Training had to be differently focused; manuals and handouts had to be revised, translated and back‐translated; and supervision had to be delivered at a distance to maintain the fidelity of the program. The international group will outline their experience of running trials in their own countries with the NFPP in a face‐to‐face format (Denmark), a group format (Hong Kong and Japan), and a self‐help format (mainland China).